Keberlakukan Perjanjian Harta Benda Perkawinan yang Dibuat Oleh Notaris Indonesia di Luar Negeri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
The purpose of this study is to analyze the position of marital property agreements from a civil law perspective and to analyze the enforceability of marital property agreements by Indonesian notaries used abroad. The research method used in this study is a normative legal research method with a statutory approach and a case approach. The results of this study explain that in terms of codification, marital property agreements are regulated in Book I of the Civil Code concerning Persons, specifically in Chapter VII concerning Marriage Agreements in Articles 139-179 of the Civil Code. Although the regulations are included in Book I of the Civil Code, they are still bound by the conditions for the validity of the agreement as stated in Article 1320 of the Civil Code. Furthermore, regarding the enforceability of marital property agreements by Indonesian notaries, they cannot be enforced abroad. This is because marital property agreements concern the personal status of husband and wife in the marriage bond and regulate the legal relationship between them during the marriage, which can be determined based on the principle of nationality or the principle of territoriality depending on the country that adheres to it.Tujuan dari penelitian ini adalah menganalisis kedudukan perjanjian harta benda perkawinan dalam perspektif hukum perdata serta menganalisis keberlakukan perjanjian harta benda perkawinan oleh notaris Indonesia yang digunakan di Luar Negeri. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian ini menjelaskan bahwa Secara kodifikasi, perjanjian harta benda perkawinan diatur dalam Buku I KUHPerdata tentang Orang, tepatnya dalam Bab VII tentang Perjanjian Kawin dalam Pasal 139 – 179 KUHPerdata. Meskipun pengaturannya termasuk dalam Buku I KUHPerdata namun tetap terikat dengan syarat-syarat sahnya perjanjian yang tercantum dalam Pasal 1320 KUHPerdata. Selanjutnya terkait keberlakuan perjanjian harta benda perkawinan oleh Notaris Indonesia tidak dapat diberlakukan di luar negeri. Hal ini karena perjanjian harta benda perkawinan menyangkut status personal suami istri dalam ikatan perkawinan dan mengatur hubungan hukum di antara mereka selama perkawinan berlangsung yang dapat ditentukan berdasarkan asas nasionalitas atau asas teritorialitas tergantung negara yang menganutnya.